2019
DOI: 10.1155/2019/3401683
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Segmentation of Lower Extremity Deep Vein Thrombosis Using Convolutional Neural Network

Abstract: Objective. Deep vein thrombosis (DVT) is a disease caused by abnormal blood clots in deep veins. Accurate segmentation of DVT is important to facilitate the diagnosis and treatment. In the current study, we proposed a fully automatic method of DVT delineation based on deep learning (DL) and contrast enhanced magnetic resonance imaging (CE-MRI) images. Methods. 58 patients (25 males; 28~96 years old) with newly diagnosed lower extremity DVT were recruited. CE-MRI was acquired on a 1.5 T system. The ground truth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…However, for women without sexual activity, performing hysteroscopic electropolypectomy is very difficult. Only a few cases have discussed the protection of hymen integrity during surgery [ 6 ]. Victoria reported a case of hysteroscopic resection of endometrial polyps in a twelve-year-old girl.…”
Section: Discussionmentioning
confidence: 99%
“…However, for women without sexual activity, performing hysteroscopic electropolypectomy is very difficult. Only a few cases have discussed the protection of hymen integrity during surgery [ 6 ]. Victoria reported a case of hysteroscopic resection of endometrial polyps in a twelve-year-old girl.…”
Section: Discussionmentioning
confidence: 99%
“…Neural network research focuses on infectious diseases and autoimmune diseases, but it is also closely related to thrombotic diseases (acute myocardial infarction). 17,18 NETs are a newly discovered neutrophil bactericidal mechanism that activates neutrophils to release chromatin and then combine with the gingival sulcus to form a new defence network against gingival plaque bacteria. 19 It has been reported 20,21 that under the induction of IL-8, LPS and interferon, the neutrophil nucleus is deformed, the chromatin is homogeneous, the nuclear membrane is broken, the nuclear material is directly in contact with the particles, forming a mixture, and finally the cell membrane is broken and NETs are released.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the proposed method is relatively effective and quick. If further improved, this method will help clinicians to evaluate DVT quickly and objectively [68].…”
Section: Artificial Intelligence In Venous Thromboembolismmentioning
confidence: 99%